TRANSPORTASI TRADISIONAL DESA LUBUK BEDORONG 1950 – 2002 - Tasya Billa; Ulul Azmi (Universitas Batanghari Jambi, 2026)
This research purposes are to explain the emergence and development of traditional transportation in Lubuk Bedorong Village and to describe the economic life of traditional transportation owners in Lubuk Bedorong Village. The method used in this research is a historical research method consisting of several stages: heuristics, criticism, interpretation, and historiography. The author sought and collected all sources that could provide information on the research topic, including written, oral, and artifacts. Written sources include the personal archives of traditional transportation owners (photos of the boat, sampan, tempek, and ketek), village archives, theses, journals, and books obtained through library research and the internet (Google Scholar). While artifacts/objects were obtained through physical observations of the three traditional modes of transportation. The results show: First, traditional transportation using river transportation in Lubuk Bedorong Village has been around since 1950 and still exists today, although only a few remain. Second, the dynamics/development of each traditional transportation are different, namely the boat, sampan, and ketek show a condition of decline but still survive at the lowest point in number, while the tempek is in a state of decline to extinction/no longer exists.